EnLIGHTenment of tumor vessel normalization and immunotherapy in glioblastoma1. Issue 1 (5th July 2018) - Treps, Lucas
Abstract: Glioblastoma multiforme (GBM) is a highly vascularized and aggressive brain tumor. Despite aggressive standard care, GBM remains predominantly fatal; hence, new innovative therapies are required. Recent research published in the Journal of Pathology has identified the CGKRK peptide as a promising tool with which to specifically target the tumor vasculature from high‐grade glioma. This tumor vessel‐homing peptide was fused to the tumor necrosis factor superfamily member LIGHT/TNFSF14, and injected intravenously into murine orthotopic GBM models. After treatment, the tumor vasculature appeared to be less abnormal, with normalized features such as increased endothelial barrier integrity, pericyte contractility, and tumor perfusion. Moreover, CGKRK–LIGHT induced the appearance of high endothelial venules (HEVs), which are specialized structures that play a role in lymphocyte trafficking and have been shown to increase T‐cell infiltration in solid tumors. Combining CGKRK–LIGHT with anti‐angiogenic and immune checkpoint blockade treatments boosted HEV induction and cytotoxic T‐cell infiltration, leading to a reduction in tumor burden. In this Commentary, I highlight the therapeutic opportunities provided by and the current limitations of LIGHT‐vascular targeting peptide as a new approach to target GBM and enhance tumor vessel delivery and immunotherapy efficacy. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd. Abstract : Linked Article: He et al J Pathol 2018;245: 209–221